(untitled) (Conference on English Language Teaching, 2023)
Children’s literary works play a role in the process of child development. Reading children’s literature is like presenting an aesthetic experience for children. The imaginative language used will foster intellectual and emotional responses in children. Therefore, it is important to provide children’s literature as their reading. Like literature in general, children’s literature is also a picture of life. In the storyline, there are life values that have benefits for children’s development, such as psychological values. The psychological aspects experienced by the story characters become meaningful learning for the psychological development of children. Based on this explanation, teaching psychological values in children’s literature needs to be done to children. This research is a qualitative descriptive research with a literary psychology approach. The data used includes primary data and secondary data. Primary data, namely a collection of short stories One Million Banyumas Children’s Stories, while secondary data is in the form of references that are relevant to the research focus. Data collection is done by library research. The data analysis technique is in the form of content analysis. The results showed that the child characters in the collection of Sejuta Cerita Anak Banyumas experienced psychological problems due to the pandemic situation that had hit the world. Psychological problems experienced by the child characters such as fear, anxiety, boredom, hopelessness, sadness, and trauma.